VERIFICATION OF THE EFFICIENCY OF A DISTRIBUTED SYSTEM FOR ADAPTIVE TRAFFIC FLOW CONTROL BASED ON EVENT-COUPLED AUTOMATIC MODELS - D. M. Elkin (Современная наука и инновации, 2023)
The paper describes the process of creating a test environment and testing a distributed system for adaptive traffic control. A software system has been developed that communicates the control system with a simulation model and a program that implements the operation of the control system. The main content of the work is the description of experiments carried out to test the effectiveness of the proposed method for the development of distributed systems for adaptive traffic control. The developed system is compared with existing systems for adaptive traffic control.